2014
DOI: 10.1182/blood-2013-03-489351
|View full text |Cite
|
Sign up to set email alerts
|

G protein–dependent basal and evoked endothelial cell vWF secretion

Abstract: Key Points Gα12 interaction with α-SNAP regulates basal EC vWF secretion. PAR-1 activation-dependent signaling via Gα12/RhoA and Gαq/11 enhances vWF secretion.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
33
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 26 publications
(33 citation statements)
references
References 44 publications
0
33
0
Order By: Relevance
“…Rusu et al have previously demonstrated that the interaction between soluble N‐ethylmaleimide sensitive factor‐attachment protein alpha (αSNAP) and guanine nucleotide‐binding alpha‐subunit 12 (Gα12) is necessary for both the basal and thrombin‐induced secretion of vWF from endothelial cells. Recently, Rusu et al have reported that, through the generation of an inhibitory peptide targeted against αSNAP, the direct interaction between αSNAP and Gα12 could be hindered .…”
Section: Systemic Role Of Vwf In Coagulopathy and Inflammation Followmentioning
confidence: 99%
See 1 more Smart Citation
“…Rusu et al have previously demonstrated that the interaction between soluble N‐ethylmaleimide sensitive factor‐attachment protein alpha (αSNAP) and guanine nucleotide‐binding alpha‐subunit 12 (Gα12) is necessary for both the basal and thrombin‐induced secretion of vWF from endothelial cells. Recently, Rusu et al have reported that, through the generation of an inhibitory peptide targeted against αSNAP, the direct interaction between αSNAP and Gα12 could be hindered .…”
Section: Systemic Role Of Vwf In Coagulopathy and Inflammation Followmentioning
confidence: 99%
“…By preventing this interaction, the researchers demonstrated decreased membrane fusion events of WPBs and, therefore, less vWF secretion. When the inhibitory peptide was tested in mice that had undergone a cecal ligation and puncture (CLP) to induce sepsis, there were both reduced plasma vWF levels and markers of microvascular thrombosis of the kidney . Furthermore, it was found that while all wild‐type mice had died by 96 hours in the CLP model, homozygous Gα12 knockouts demonstrated reduced vWF levels and 100% survival.…”
Section: Systemic Role Of Vwf In Coagulopathy and Inflammation Followmentioning
confidence: 99%
“…Although the storage of VWF in WPB of endothelial cells has been known for decades, the molecular mechanisms governing WPB docking with plasma membrane and VWF secretion remained poorly understood. Using a combination of pharmacological, genetic, and molecular techniques, Rusu et al dissected a mechanism for VWF secretion from endothelial cells mediated via Gαq/11 and Gα12 that can be triggered during basal or stimulated conditions [41]. In addition, Bierings et al reported the Rab27A effector synaptotagmin-like protein 4-a (Slp4-a) plays a critical role in regulating hormone-evoked WPB exocytosis [42].…”
Section: Regulation Of Vwf Protein Secretionmentioning
confidence: 99%
“…Among these, the implication of a series of intracellular proteins (including but not limited to: RalA, Rab3, Rab27a, Rab15, Rab33a, Rab37, Munc13-4, Munc18c, Slp4a, Annexin A2-S100A10, syntaxin-binding protein 1, syntaxin-4, VAMP-3, G proteins) has been documented based on the finding that deletion or mutation of these proteins modulates constitutive and/or regulated release of VWF. 44,[65][66][67][68][69][70][71][72][73] Recently, an unexpected and novel type of regulation of VWF release has been reported by Torisu and colleagues. 74 Not only did they observe that WPBs are often in close proximity of autophagosomes but they also detected the presence of VWF in these organelles.…”
mentioning
confidence: 99%